Fundamentals of Software Engineering Third IPM International Conference, FSEN 2009, Kish Island, Iran, April 15-17, 2009, Revised Selected Papers - Arbab, Farhad; Sirjani, Marjan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Conference on Fundamentals of Software Engineering, FSEN 2009, held in Kish Island, Iran, in April 2009. The 22 revised full papers and 5 revised short papers presented together with 3 invited lectures were carefully reviewed and selected from 88 submissions. The topics include models of programs and systems, software specification, validation and verification, software architectures and their description languages, object and multi-agent systems, coordination and feature interaction, integration of formal and informal methods, integration of different formal methods, component-based development, service-oriented development, model checking and theorem proving, software and hardware verification and CASE tools and tool integration.
Session 1. Invited Papers -- A Process-Theoretic Look at Automata -- Verification, Performance Analysis and Controller Synthesis for Real-Time Systems -- rCOS: Theory and Tool for Component-Based Model Driven Development -- Session 2. Regular Papers -- Termination in Higher-Order Concurrent Calculi -- Typing Asymmetric Client-Server Interaction -- Equational Reasoning on Ad Hoc Networks -- Towards a Notion of Unsatisfiable Cores for LTL -- Rule Formats for Determinism and Idempotence -- The Complexity of Reachability in Randomized Sabotage Games -- Applying Step Coverability Trees to Communicating Component-Based Systems -- Program Logics for Sequential Higher-Order Control -- Modular Schedulability Analysis of Concurrent Objects in Creol -- A Timed Calculus for Wireless Systems -- Model Checking Linear Duration Invariants of Networks of Automata -- Automata Based Model Checking for Reo Connectors -- On the Expressiveness of Refinement Settings -- Bounded Rational Search for On-the-Fly Model Checking of LTL Properties -- Automated Translation and Analysis of a ToolBus Script for Auctions -- Executable Interface Specifications for Testing Asynchronous Creol Components -- Compositional Strategy Mapping -- A Sound Analysis for Secure Information Flow Using Abstract Memory Graphs -- Refinement Patterns for Hierarchical UML State Machines -- Specification and Validation of Behavioural Protocols in the rCOS Modeler -- The Interplay between Relationships, Roles and Objects -- A Coordination Model for Interactive Components -- Session 3. Short Papers -- Evolution Control in MDE Projects: Controlling Model and Code Co-evolution -- An xADL Extension for Managing Dynamic Deployment in Distributed Service Oriented Architectures -- A First Step towards Security Policy Compliance of Connectors -- A Safe Implementation of Dynamic Overloading in Java-Like Languages -- Fundamental Concepts for the Structuring of Functionality into Modular Parts.
Keywords: Computer science; Software engineering; Logic design; Computer Science; Software Engineering/Programming and Operating Systems; Logics and Meanings of Programs; Programming Techniques; Models and Principles